2007
DOI: 10.1002/ejic.200700804
|View full text |Cite
|
Sign up to set email alerts
|

Using Chiral Ligand Substituents To Promote the Formation of Dinuclear, Double‐Stranded Iron, Manganese, and Zinc Mesocates

Abstract: The synthesis and structures of dinuclear manganese, iron, and zinc complexes of chiral di-iminodipyrromethane ligands (L) are reported. Schiff base condensation reactions between 5,5Ј-diformyl-2,2Ј-dipyrromethane and the chiral amines (-)-(R)-CH(Me)tBu and (+)-(R)-CH(Me)Ph result in the straightforward synthesis of the new, chiral ligands H 2 L 2 and H 2 L 3 , respectively. Salt elimination reactions between K 2 L and divalent Mn and Fe halides, and protonolysis reactions be-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 28 publications
(29 reference statements)
0
11
0
Order By: Relevance
“…9,10 Furthermore, we found that the use of chiral imine-nitrogen substituents derived from chiral amines promoted the sole formation of diastereomeric dinuclear mesocates instead of the expected helicates. 11 While investigating the mechanism of formation of these dinuclear complexes, we isolated the octahedral mononuclear complex [Mn(HL) 2 ] in which one half of the ligand had undergone an imine-pyrrole to amine-azafulvene tautomerisation and in which the pendant amine groups appeared accessible to the second metal reagent. 9 Here we describe the synthesis, structures, and reactions of the 1:1 complexes [MX 2 (H 2 L)] formed between the tetradentate ligand H 2 L and the transition metal halides MX 2 (M = Fe, X = Br; M = Co, Zn, X = Cl) in which tautomerisation has resulted in the presence of pendant amine groups that can be exploited as hydrogen bond donors to the ancillary ligands.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Furthermore, we found that the use of chiral imine-nitrogen substituents derived from chiral amines promoted the sole formation of diastereomeric dinuclear mesocates instead of the expected helicates. 11 While investigating the mechanism of formation of these dinuclear complexes, we isolated the octahedral mononuclear complex [Mn(HL) 2 ] in which one half of the ligand had undergone an imine-pyrrole to amine-azafulvene tautomerisation and in which the pendant amine groups appeared accessible to the second metal reagent. 9 Here we describe the synthesis, structures, and reactions of the 1:1 complexes [MX 2 (H 2 L)] formed between the tetradentate ligand H 2 L and the transition metal halides MX 2 (M = Fe, X = Br; M = Co, Zn, X = Cl) in which tautomerisation has resulted in the presence of pendant amine groups that can be exploited as hydrogen bond donors to the ancillary ligands.…”
Section: Introductionmentioning
confidence: 99%
“…To produce a “true” helicate assembly, the ligand must adopt an S‐type arrangement where each of the metal binding domains coordinates a different metal ion but the ligand twists in the centre, generating the homochiral (ΔΔ or ΛΛ) helicate. If the ligand coordinates two different metal ions but the ligand strand does not twist (referred to as a C‐type arrangement) then this “side‐by‐side” complex is referred to as the achiral (ΔΛ or ΛΔ) meso helicate (or mesocate) …”
Section: Figurementioning
confidence: 99%
“…In fact, only a very limited number of (2-iminopyrrolyl) iron complexes have been reported in the literature, the majority of them possessing complicated and bulky 2-iminopyrrolyl ligands not presenting a clear evidence for their molecular structure. [5,29,30] This was only achieved in 2014, when Gomes et al prepared the first bis(2-iminopyrrolyl) iron(II) complex with the support of pyridine coordination. [31] It is more difficult to isolate homoleptic bis(2-iminopyrrolyl) iron(II) complexes because they are very unsaturated 14 valence electrons iron intermediate with 14 valence electrons species, thus not being stable.…”
Section: Introductionmentioning
confidence: 99%
“…In the coordination chemistry of 2‐iminopyrrolyl ligand, iron is in a special situation. In fact, only a very limited number of (2‐iminopyrrolyl) iron complexes have been reported in the literature, the majority of them possessing complicated and bulky 2‐iminopyrrolyl ligands not presenting a clear evidence for their molecular structure 5,29,30. This was only achieved in 2014, when Gomes et al prepared the first bis(2‐iminopyrrolyl) iron(II) complex with the support of pyridine coordination 31.…”
Section: Introductionmentioning
confidence: 99%